Formulation and Monitoring the Stability of Artesunate in Artesunate - Amodiaquine Combination Tablets - Danso – Mensah, Stephen (2012)
A thesis submitted to the Department of Pharmaceutical Chemistry, Kwame Nkrumah University of Science and Technology in partial fulfillment of the requirements for the degree of